Pengaruh Mekanisme Bonus, Debt Covenant, dan Profitabilitas terhadap Transfer Pricing: (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Tysan Parawansyah Syailendra; Martini Martini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of bonus mechanisms, debt covenants, and profitability on transfer pricing. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in their financial reports for the 2019-2023 period. The sampling technique in this research used a purposive sampling method and a sample of 57 companies was obtained. The analysis technique used is multiple linear regression analysis using SPSS version 22.0 software. The results of this research show that the bonus and debt covenant mechanism has a positive and significant effect on transfer pricing and profitability has a negative and significant effect on transfer pricing.